2013
DOI: 10.1016/s1743-9191(13)60023-0
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine breast cancer: retrospective analysis of 96 patients and review of literature

Abstract: This study showed a better prognosis in patients with NEBC compared with breast carcinomas with a minor neuroendocrine component and with conventional invasive ductal or lobular cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 43 publications
3
41
2
Order By: Relevance
“…Günhan-Bilgen et al [9] and Lopez-Bonet et al [5] found that these tumors represent 0.27% and 0.51% of breast cancer cases respectively. More recently, in Rovera et al's report [6], among 2829 patients who underwent surgery for breast cancer, there were 61 patients with NEBC. According to the WHO, the incidence of NEBC is less than 1% [4].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Günhan-Bilgen et al [9] and Lopez-Bonet et al [5] found that these tumors represent 0.27% and 0.51% of breast cancer cases respectively. More recently, in Rovera et al's report [6], among 2829 patients who underwent surgery for breast cancer, there were 61 patients with NEBC. According to the WHO, the incidence of NEBC is less than 1% [4].…”
Section: Discussionmentioning
confidence: 99%
“…In Bonet's report [5], the median age was 63 years .Only one patient was 35 years old, the rest of the patients were above 50 years old. Rovera [6] reports a mean age at diagnosis of 70 years, and 90.5% of the patients were in menopause. In agreement with previous reports, our patient had 77 years old.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations